2016
DOI: 10.1177/1359104515603216
|View full text |Cite
|
Sign up to set email alerts
|

A first-level evaluation of a school-based family programme for adolescent social, emotional and behavioural difficulties

Abstract: This study is a first-level evaluation of an intervention targeted at adolescents with social, emotional and behavioural difficulties in Irish post-primary schools. It is a combined implementation of the Working Things Out adolescent programme and the Parents Plus Adolescent Programme (WTOPPAP). Overall, 47 parents and their children (mean age: 13.81 years) took part in the study. The study used a repeated measures design to assess change at pre- and post-intervention and 5-month follow-up using the Strengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Four studies of the PP Adolescents Program have been conducted. In two of these adolescents attended the Working Things Out Program, while their parents concurrently attended the PP Adolescents Program (Rickard et al., ; Wynne, Brosnan, Doyle, Kenny, & Sharry, ). There were also conjoint family sessions held midway through these programs and at the end of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies of the PP Adolescents Program have been conducted. In two of these adolescents attended the Working Things Out Program, while their parents concurrently attended the PP Adolescents Program (Rickard et al., ; Wynne, Brosnan, Doyle, Kenny, & Sharry, ). There were also conjoint family sessions held midway through these programs and at the end of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There were also conjoint family sessions held midway through these programs and at the end of treatment. Two studies were run in child and adolescent mental health clinics with families of adolescents with psychological disorders (Beattie, O'Donohoe, Guerin, & Fitzpatrick, ; Wynne et al., ), and two were conducted in schools (Nitsch et al., ; Rickard et al., ). In a nonrandomized controlled trial of families of adolescents with disruptive behavior disorders, emotional disorders, and developmental disabilities attending mental health clinics at two Dublin university hospitals, Beattie et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may contribute to defining the type of intervention and services that will be most helpful to the child and the family, to determine extraneous variables that may affect the child during treatment and also to measure intervention effectiveness both during and after treatment (Lessenberry and Rehfeldt, 2004). The Parental Stress Scale (PSS) developed by Berry and Jones (1995) has been widely used to assess change after parent and/or family intervention programmes for parents of children and adolescents with social, emotional and behavioural difficulties and/or developmental disabilities (Bazzano et al, 2015; Caldwell et al, 2007; Coughlin et al, 2009; Griffin et al, 2010; Rickard et al, 2016; Tellegen and Sanders, 2014; Wynne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the research on family‐based interventions or parenting programs has involved indicated or selective approaches to prevention (Baldwin et al ., ; Carr et al ., ; Chu et al ., ; Furlong et al ., ), and most parent training programs were originally developed with parents of younger children in mind (Eyberg et al ., ; Kumpfer, Whiteside, Greene & Allen, ; Ralph, Winston Tournbourou, Grigg, Mulcahy, Carr‐Gregg & Sanders, ). There is a gap in research into interventions offered universally to parents of adolescents (Chu et al ., ; Eyberg et al ., ; Furlong et al ., ), but some such studies have shown positive effects such as improved parenting confidence (Chu et al ., ), communication (Leijten, Raaijmakers, De Castro & Matthys, ), parental satisfaction (Rickard, Brosnan, O'Laoide et al ., ) and reduced dysfunctional disciplining behavior (Leijten et al ., ), adolescent problem behavior (Chu et al ., ), and adolescent emotional difficulties (Rickard et al ., ). An evaluation of a telephone helpline indicated that most parents appreciated this type of support for both practical parenting advice and information on where to seek further support (Henricson & Roker, ).…”
Section: Introductionmentioning
confidence: 99%